Method for manufacturing pulp fiber raw material for fiber composite reinforced material, pulp fiber raw material for fiber composite reinforced material, fiber composite reinforced material, pellet, film, fiber, nonwoven fabric

By supplying ozone-containing gas to the treatment liquid of recirculated pulp fibers to reduce the hemicellulose content, the problem of difficulty in using recirculated pulp fibers in the prior art is solved, and a material containing cellulose nanofibers is easily formed.

CN114269535BActive Publication Date: 2025-03-11UNI CHARM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080059567.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2020-08-31
Publication Date
2025-03-11
Estimated Expiration
2040-08-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use recirculated pulp fibers to produce fiber composite reinforcement materials containing cellulose nanofibers, and the performance of fiber composite reinforcement materials is insufficient.

Method used

By supplying ozone-containing gas to the treatment liquid containing recirculated pulp fibers, the hemicellulose content of the pulp fibers is reduced to form a pulp fiber raw material having a hemicellulose content of less than 8.0 mass %.

Benefits of technology

The pulp fiber raw material with low hemicellulose content is realized, and the fiber composite reinforcement material containing cellulose nanofibers is easily formed, which improves the performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114269535B_ABST
    Figure CN114269535B_ABST
Patent Text Reader

Abstract

The purpose of the present disclosure is to provide a method for manufacturing a pulp fiber raw material having a low hemicellulose content and capable of easily forming a fiber composite reinforcement material containing cellulose nanofibers. The manufacturing method of the present disclosure is as follows. A method for manufacturing a pulp fiber raw material for a fiber composite reinforcement material containing cellulose nanofibers from pulp fibers to be treated, characterized in that the method includes a pulp fiber raw material forming step: by supplying ozone-containing gas to a treatment liquid containing the above-mentioned pulp fibers to be treated, the above-mentioned pulp fiber raw material having a hemicellulose content of less than 8.0% by mass is formed from the above-mentioned pulp fibers to be treated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing a pulp fiber raw material for a fiber composite reinforcement material containing cellulose nanofibers from pulp fibers to be processed, a pulp fiber raw material for a fiber composite reinforcement material containing cellulose nanofibers, and a fiber composite reinforcement material containing cellulose nanofibers derived from the pulp fiber raw material, and pellets, films, fibers and nonwoven fabrics containing the fiber composite reinforcement material. Background Art

[0002] A technology for recycling used sanitary products such as disposable diapers was studied.

[0003] For example, Patent Document 1 discloses a method for producing recycled pulp that can be reused mainly as sanitary products. Specifically, Patent Document 1 describes a method in which pulp fibers are recovered from used sanitary products containing pulp fibers and superabsorbent polymers to produce recycled pulp that can be reused as sanitary products, and the method is characterized in that the method includes the following steps: a step of decomposing the used sanitary products into pulp fibers and other raw materials by subjecting the used sanitary products to a physical force in an aqueous solution containing polyvalent metal ions or an acidic aqueous solution having a pH of 2.5 or less; a step of separating the pulp fibers from a mixture of the pulp fibers and other raw materials generated in the decomposition step; and a step of treating the separated pulp fibers with an ozone-containing aqueous solution having a pH of 2.5 or less.

[0004] In Patent Document 1, the reason for treating pulp fibers with an ozone-containing aqueous solution is that a large amount of highly absorbent polymers remain in the separated pulp fibers, and the highly absorbent polymers are oxidatively decomposed to make them soluble and thus removed from the pulp fibers. Patent Document 1 discloses a method of treating pulp fibers with an ozone-containing aqueous solution, which includes adding an ozone-containing aqueous solution to a treatment tank and adding the separated pulp fibers to the ozone-containing aqueous solution. In the above method, during the treatment, the ozone-containing aqueous solution is preferably stirred appropriately to form a water flow, or ozone gas may be blown into the aqueous solution placed in a container to generate a water flow in the ozone-containing aqueous solution by the rising bubbles of the ozone gas.

[0005] In addition, fiber composite reinforced materials containing cellulose fibers have been studied. For example, Patent Document 2 discloses a composite resin composition, characterized in that it is a resin composition used as a raw material for a molded product formed by a molding machine, which contains a main resin and a fibrous filler, the ends of the fiber length direction of the fibrous filler are defibrated, the defibrated portion is 5% or more and 50% or less of the fiber length of the entire fibrous filler, the fiber diameter in the defibrated portion of the fibrous filler is 1 / 1000 or more and 1 / 10 or less of the fiber diameter in the portion that is not defibrated, the aspect ratio in the portion that is not defibrated of the fibrous filler is 5 or more and 1000 or less, and the elastic modulus of the fibrous filler is greater than the elastic modulus of the main resin, and the difference is within 20 GPa.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2016-881

[0009] Patent Document 2: Japanese Patent Application Publication No. 2018-115254 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] Patent Document 1 describes the reuse of “recycled pulp fibers” as “pulp fibers” themselves, but Patent Document 1 does not describe the use of recycled pulp fibers as a raw material, particularly a pulp fiber raw material for fiber composite reinforcement materials containing cellulose nanofibers.

[0012] In sanitary products, absorbents and the like mostly use pulp fibers, and the pulp fibers mostly use pulp fibers derived from coniferous trees. It is known that in addition to about 50% to about 60% by mass of cellulose, pulp fibers derived from coniferous trees also contain about 10% to about 25% by mass of hemicellulose. Hemicellulose is mostly contained in the cell walls of plants. Therefore, if pulp fibers are directly used as pulp fiber raw materials for fiber composite reinforcement materials containing cellulose nanofibers, cellulose nanofibers cannot be formed from pulp fibers, and the performance of the fiber composite reinforcement materials may be insufficient.

[0013] It should be noted that in the field of sanitary products, pulp fibers are used for absorbent bodies, etc., and hemicellulose contained in pulp fibers is usually not removed from the pulp fibers from the viewpoints of (i) not easily hindering the functions of sanitary products (such as absorbency), (ii) imparting elasticity to the pulp fibers, and (iii) contributing to the yield of the manufactured pulp fibers.

[0014] In the composite resin composition described in Patent Document 2, the ends of the fibrous filler in the longitudinal direction of the fibers are defibrated, but the entire fibrous filler is not fibrillated, for example, cellulose is not nanofibrillated, and there is still room for improvement as a fiber composite reinforced material.

[0015] Therefore, an object of the present disclosure is to provide a method for producing a pulp fiber raw material having a low hemicellulose content and capable of easily forming a fiber composite reinforcing material containing cellulose nanofibers.

[0016] Solutions for solving problems

[0017] The present inventors have discovered a method for manufacturing pulp fiber raw materials for fiber composite reinforcement materials containing cellulose nanofibers from pulp fibers to be treated, characterized in that the method includes a pulp fiber raw material forming step: by supplying ozone-containing gas to a treatment liquid containing the above-mentioned pulp fibers to be treated, the above-mentioned pulp fiber raw materials having a hemicellulose content of less than 8.0% by mass are formed from the above-mentioned pulp fibers to be treated.

[0018] Effects of the Invention

[0019] The method for producing a pulp fiber raw material disclosed in the present invention can produce a pulp fiber raw material having a low hemicellulose content and capable of easily forming a fiber composite reinforcement material containing cellulose nanofibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a flow chart representing an embodiment of the method of the present disclosure.

[0021] Figure 2 Yes means Figure 1 A schematic diagram of a structural example of an apparatus for an ozone treatment step.

[0022] Figure 3 Yes means Figure 1 A schematic diagram of another structural example of an apparatus for an ozone treatment process.

[0023] Figure 4 Yes means Figure 1 A schematic diagram of another structural example of an apparatus for an ozone treatment process. DETAILED DESCRIPTION

[0024] The present disclosure specifically relates to the following aspects.

[0025] [Method 1]

[0026] A method for producing pulp fiber raw materials for fiber composite reinforcement materials containing cellulose nanofibers from pulp fibers to be processed, characterized in that:

[0027] The method includes a pulp fiber raw material forming step: supplying ozone-containing gas to a treatment liquid containing the pulp fibers to be treated to form the pulp fiber raw material having a hemicellulose content of less than 8.0 mass % from the pulp fibers to be treated.

[0028] When the above-mentioned manufacturing method is used, a pulp fiber raw material having a predetermined hemicellulose content is manufactured from the pulp fiber to be processed, so that the hemicellulose contained in the pulp fiber raw material is not likely to hinder the formation of cellulose nanofibers from the pulp fiber raw material. Therefore, the above-mentioned manufacturing method can manufacture a pulp fiber raw material that can easily form a fiber composite reinforcement material containing cellulose nanofibers.

[0029] In addition, when the pulp fiber raw material having a specified hemicellulose content produced by the above production method is mixed with a molten resin, the hemicellulose is less likely to be thermally denatured, and the fiber composite reinforcement formed from the above pulp fiber raw material is less likely to contain coloring derived from thermally denatured hemicellulose.

[0030] [Method 2]

[0031] The method according to Embodiment 1, wherein the pulp fiber raw material has a lignin content of 0.10 mass % or less.

[0032] It is known that pulp fibers may contain lignin in addition to cellulose. For example, coniferous trees, which are often used in sanitary products, are known to contain 20 to 30% by mass of lignin.

[0033] In the above-mentioned manufacturing method, since the pulp fiber raw material having a predetermined lignin content is manufactured from the pulp fiber to be processed, the lignin contained in the pulp fiber raw material is not likely to hinder the formation of cellulose nanofibers from the pulp fiber raw material. Therefore, the above-mentioned manufacturing method can manufacture a pulp fiber raw material that can easily form a fiber composite reinforcement material containing cellulose nanofibers.

[0034] In addition, when the pulp fiber raw material having a predetermined lignin content produced by the above production method is mixed with a molten resin, the lignin is less likely to be thermally denatured, and the fiber composite reinforcement formed from the above pulp fiber raw material is less likely to contain coloring derived from thermally denatured lignin.

[0035] [Method 3]

[0036] The method according to embodiment 1 or 2, wherein the pulp fibers to be treated are pulp fibers contained in used sanitary products.

[0037] In the above-mentioned manufacturing method, since the pulp fibers to be treated are the pulp fibers contained in used sanitary products, in the pulp fiber raw material forming step, the pulp fibers contained in the used sanitary products are washed, sterilized, bleached, etc., and when the above-mentioned treatment liquid contains a highly absorbent polymer, the highly absorbent polymer is decomposed and made soluble, thereby manufacturing a pulp fiber raw material that can easily form a fiber composite reinforcement material containing cellulose nanofibers.

[0038] [Method 4]

[0039] The method according to any one of aspects 1 to 3, further comprising the step of manufacturing a fiber composite reinforced material: manufacturing the fiber composite reinforced material from the pulp fiber raw material and a resin.

[0040] When the above-mentioned production method is used, a fiber composite reinforcement material can be efficiently produced from the pulp fibers to be treated.

[0041] The above-mentioned manufacturing method includes: (i) a method of forming cellulose nanofibers from pulp fibers to be treated and mixing the cellulose nanofibers with a resin; (ii) a method of mixing a pulp fiber raw material and a resin and dispersing the cellulose nanofibers derived from the pulp fiber raw material into the resin; (iii) a method of forming cellulose fibers from pulp fibers to be treated, mixing the cellulose fibers and a resin and dispersing the cellulose nanofibers derived from the pulp fiber raw material into the resin, etc.

[0042] [Method 5]

[0043] The method according to Embodiment 4, wherein in the fiber composite reinforced material production step, the pulp fiber raw material and the resin are mixed to disperse the cellulose nanofibers derived from the pulp fiber raw material in the resin.

[0044] In the above production method, in the fiber composite reinforced material production step, the pulp fiber raw material and the resin are mixed to disperse the cellulose nanofibers derived from the pulp fiber raw material in the resin, so that the fiber composite reinforced material can be efficiently produced from the pulp fiber to be processed.

[0045] [Method 6]

[0046] The method according to Embodiment 5, wherein the pulp fiber raw material and the resin are mixed in a dry manner.

[0047] In the above-mentioned manufacturing method, the pulp fiber raw material and the resin are mixed in a dry manner. Therefore, compared with the method of forming cellulose nanofibers from the pulp fiber raw material once and then mixing the cellulose nanofibers with the resin according to the well-known method such as the wet method, the fiber composite reinforcement material can be effectively manufactured from the pulp fiber to be processed.

[0048] [Method 7]

[0049] A pulp fiber raw material, characterized in that it is a pulp fiber raw material for a fiber composite reinforcement material containing cellulose nanofibers, and the pulp fiber raw material has a hemicellulose content of less than 8.0% by mass.

[0050] Since the pulp fiber raw material has a predetermined hemicellulose content, when the pulp fiber raw material and molten resin are mixed to form a fiber composite reinforcement material, the hemicellulose is less likely to be thermally denatured, and the fiber composite reinforcement material formed from the pulp fiber raw material is less likely to contain coloring derived from thermally denatured hemicellulose.

[0051] [Method 8]

[0052] The pulp fiber raw material according to aspect 7, wherein the pulp fiber raw material has a lignin content of 0.10 mass % or less.

[0053] Since the pulp fiber raw material has a predetermined lignin content, when the pulp fiber raw material and molten resin are mixed to form a fiber composite reinforcement material, the lignin is less likely to be thermally denatured, and the fiber composite reinforcement material formed from the pulp fiber raw material is less likely to contain coloring derived from thermally denatured lignin.

[0054] [Method 9]

[0055] The pulp fiber raw material according to any one of aspects 7 and 8, wherein the pulp fiber raw material is derived from used sanitary products containing pulp fibers.

[0056] Since the pulp fiber raw material is derived from used sanitary products containing pulp fibers, it is possible to easily form a fiber composite reinforcement material containing cellulose nanofibers.

[0057] [Method 10]

[0058] A fiber composite reinforcement material comprising a resin and cellulose nanofibers derived from the pulp fiber raw material according to any one of aspects 7 to 9.

[0059] The fiber composite reinforced material has high dispersibility of cellulose nanofibers and excellent properties such as strength.

[0060] [Method 11]

[0061] A pellet containing the fiber composite reinforcement material described in embodiment 10.

[0062] The pellets can be easily formed into a fiber composite reinforcement material containing cellulose nanofibers.

[0063] [Method 12]

[0064] A film comprising the fiber composite reinforcement material according to embodiment 10.

[0065] Since the film contains the fiber composite reinforcement material, it is excellent in performance, such as strength.

[0066] [Method 13]

[0067] A fiber comprising the fiber composite reinforcement material according to embodiment 10.

[0068] Since the fibers contain the fiber composite reinforcing material, they are excellent in performance, for example, strength.

[0069] [Method 14]

[0070] A nonwoven fabric comprising the fiber composite reinforcement material according to embodiment 10.

[0071] Since the nonwoven fabric contains the fiber composite reinforcing material, it is excellent in performance, for example, strength.

[0072] A method for producing a pulp fiber raw material for a fiber composite reinforcement material containing cellulose nanofibers from pulp fibers to be treated (hereinafter sometimes simply referred to as a "method for producing a pulp fiber raw material") will be described.

[0073] In the present disclosure, the pulp fiber to be treated is not particularly limited as long as it contains 8.0% by mass or more of hemicellulose. For example, it preferably contains 8.5% by mass or more of hemicellulose, more preferably 9.0% by mass or more, further preferably 9.5% by mass or more, and further more preferably 10.0% by mass or more.

[0074] In the present disclosure, the pulp fiber to be treated contains lignin in an amount of preferably 0.5 mass % or more, more preferably 1.0 mass % or more, further preferably 2.0 mass % or more, further more preferably 3.0 mass % or more, and further more preferably 4.0 mass % or more.

[0075] Examples of the pulp fibers to be treated include wood pulp (eg, conifer pulp, hardwood pulp), cross-linked pulp, and non-wood pulp.

[0076] In addition, the pulp fibers to be treated may be pulp fibers contained in used sanitary products.

[0077] The used sanitary products mentioned above refer to sanitary products after use by the user, including sanitary products in a state of absorbing the user's liquid excrement, sanitary products that have been used but have not absorbed the excrement, and sanitary products that have been discarded without being used.

[0078] It should be noted that, in this specification, the term "to be treated" of pulp fibers to be treated is a modifier used to distinguish pulp fibers before treatment from pulp fiber raw materials after treatment, and has no other intention.

[0079] In the present specification, examples of “pulp fibers to be processed” include used pulp fibers, particularly pulp fibers derived from used sanitary products, and therefore “pulp fibers to be processed” are sometimes simply referred to as “pulp fibers”.

[0080] The structural example of sanitary products is described. For example, sanitary products include a liquid-permeable sheet, a liquid-impermeable sheet, and an absorbent body disposed between the liquid-permeable sheet and the liquid-impermeable sheet. Examples of sanitary products include diapers, urine-absorbing pads, sanitary napkins, bed sheets, pet pads, and the like.

[0081] Examples of the constituent member of the liquid-permeable sheet include nonwoven fabrics or films, and specifically, liquid-permeable nonwoven fabrics, synthetic resin films having liquid-permeable pores, and composite sheets thereof. Examples of the constituent member of the liquid-impermeable sheet include nonwoven fabrics or films, and specifically, liquid-impermeable nonwoven fabrics, liquid-impermeable synthetic resin films, and composite sheets thereof.

[0082] As constituent components of the absorbent body, there are exemplified absorbent cores (e.g., pulp fibers and super absorbent polymers) and core wrappers. As pulp fibers, there are no particular restrictions as long as they can be used as sanitary products, and exemplified are cellulose-based fibers. As cellulose-based fibers, there are exemplified wood pulp (e.g., conifer pulp, hardwood pulp), cross-linked pulp, non-wood pulp, etc. As super absorbent polymers (Super Absorbent Polymer: SAP), there are no particular restrictions as long as they can be used as sanitary products, and exemplified are polyacrylate-based, polysulfonate-based, and maleic anhydride-based materials.

[0083] One surface and the other surface of the absorbent body are joined to the liquid-permeable sheet and the liquid-impermeable sheet, respectively, by means of an adhesive. When viewed from above, the portion (peripheral portion) of the liquid-permeable sheet that extends outwardly of the absorbent body in a manner to surround the absorbent body is joined to the portion (peripheral portion) of the liquid-impermeable sheet that extends outwardly of the absorbent body in a manner to surround the absorbent body by means of an adhesive. Thus, the absorbent body is wrapped inside the joint of the liquid-permeable sheet and the liquid-impermeable sheet. As an adhesive, there is no particular limitation as long as it can be used as a sanitary product and the bonding force is reduced by softening with warm water as described later, and examples thereof include hot-melt adhesives. As hot-melt adhesives, examples thereof include pressure-sensitive adhesives or heat-sensitive adhesives having a rubber-based body such as styrene-ethylene-butadiene-styrene, styrene-butadiene-styrene, styrene-isoprene-styrene, or an olefin-based body such as polyethylene.

[0084] Figure 1 This is a flow chart showing a material separation method for separating used sanitary products into constituent materials. The material separation method is a method for separating used sanitary products into films, nonwoven fabrics, pulp fibers, and highly absorbent polymers. The material separation method includes a pretreatment step S11, a decomposition step S12, and a separation step S13.

[0085] In the pre-treatment step S11, the used sanitary products are swollen with water. In the decomposition step S12, the used sanitary products that have been swollen are subjected to physical impact to decompose the used sanitary products into films, non-woven fabrics, core wraps, etc., and absorbent cores (e.g., pulp fibers and super absorbent polymers). In the separation step S13, the films, non-woven fabrics, pulp fibers, and super absorbent polymers are separated.

[0086] It should be noted that, when a mixture of pulp fibers and highly absorbent polymers (pulp fiber content) is obtained in advance by some method, the steps before the pulp fiber raw material manufacturing method among the pretreatment step S11, the decomposition step S12 and the separation step S13 are unnecessary. Each step is described below.

[0087] The pre-treatment step S11 is to keep a plurality of used sanitary products in the state of being collected from the outside, that is, not being broken or cut, and if they are rolled or folded, they are kept in this state, and the super absorbent polymer of the absorbent body is not inactivated, but is swollen by absorbing water. In this embodiment, the used sanitary products are swollen by absorbing warm water, or the absorbed water is heated after being swollen by absorbing water to form warm water. Warm water refers to water with a temperature higher than normal temperature (20°C ± 15°C (5°C to 35°C): JIS Z 8703).

[0088] Generally, the amount of liquid excrement actually absorbed by the used sanitary products is very small (for example, about 10 to 20% by mass of the maximum absorption amount) compared to the maximum absorption amount that the sanitary products can absorb. In this embodiment, in the pre-treatment step S11, the used sanitary products are immersed in warm water so that they absorb water to an amount close to the maximum absorption amount of the used sanitary products (for example, more than 80% by mass of the maximum absorption amount). Alternatively, the used sanitary products are immersed in water at room temperature, and after absorbing water to an amount close to the maximum absorption amount of the used sanitary products, the used sanitary products are heated as a whole to the temperature of warm water. Thus, the used sanitary products can be made into a very expanded state by using warm water or water at room temperature (hereinafter also referred to as "warm water"). As a result, a very high internal pressure is generated in the used sanitary products. It should be noted that the purpose of making the water warm water is mainly to weaken the bonding force of the adhesive as described later.

[0089] Here, the used sanitary product is immersed in warm water in a state where the used sanitary product is originally rolled up or folded with the liquid-impermeable sheet on the outside (the liquid-permeable sheet is hidden inside), so that the absorbent body of the used sanitary product absorbs the warm water in the warm water and expands. As a result, the internal pressure of the used sanitary product increases, and a force to open outward acts on the used sanitary product, so that the used sanitary product in the rolled up or folded state opens outward and becomes roughly flat. That is, the used sanitary product can be made to be flat and unfolded in warm water. At this time, for the used sanitary product, since the absorbent body absorbs a large amount of warm water and expands greatly, the sanitary product is in a state where any part of its surface, that is, the liquid-permeable sheet and the liquid-impermeable sheet that wrap the absorbent body, is easily broken. That is, the used sanitary product can be made into a state where any part of the surface is about to break by the pre-treatment step S11. It should be noted that when the used sanitary product is originally in a flat and unfolded state, the state is maintained to be a state where any part of the surface is easily broken. This state will not occur when the used sanitary product is broken.

[0090] Furthermore, by immersing the used sanitary products in warm water and / or absorbing warm water, the adhesive (e.g., hot melt adhesive) used for joining the components can be softened by the heat of the warm water, thereby reducing the bonding strength of the adhesive. For example, the adhesive joining the peripheral portion of the liquid-permeable sheet and the peripheral portion of the liquid-impermeable sheet can be softened by the heat of the warm water, thereby reducing the bonding strength of the adhesive. Furthermore, the adhesive joining the liquid-permeable sheet and the absorbent body and the adhesive joining the liquid-impermeable sheet and the absorbent body can be softened by the heat of the warm water, thereby reducing the bonding strength of these adhesives.

[0091] Thus, in the pre-treatment step S11, due to the expansion of the absorbent body of the used sanitary product, any part of the surface of the used sanitary product can be in a state of being about to be broken, and the bonding force of the adhesive can be in a state of being reduced. By making the used sanitary product in such a state, the used sanitary product can be reliably disassembled in the disassembly step described later.

[0092] As long as the adhesive of the used sanitary products can be softened, the temperature of the warm water in the pretreatment step S11 is not particularly limited, and for example, 60°C or more, preferably 70°C or more and 98°C or less can be cited. By setting the temperature of the warm water to 70°C or more, the adhesive that joins the components together can be further softened under the action of the heat of the warm water, and the bonding force of the adhesive can be further reduced. By setting the temperature of the warm water to 98°C or less, the warm water can be reliably present as a liquid, so that the used sanitary products can more reliably absorb the warm water. Under the action of the expansion of the absorbent body and the heat of the warm water, the state in which the surface of the used sanitary products is about to be broken and the state in which the bonding force of the adhesive is reduced can be more reliably produced. For the measurement of temperature, the temperature of the warm water in the state of being immersed in the used sanitary products is measured, or the temperature of the used sanitary products that absorb water to an amount close to the maximum absorption amount is measured at 5 mm inside the surface (the top of the inserted temperature sensor).

[0093] Furthermore, in the process of reusing used sanitary products, sterilization of the constituent materials is extremely important, and setting the temperature of the warm water to 70° C. or higher is preferred because it can also achieve the effect of sterilizing (disinfecting) the used sanitary products.

[0094] As long as the absorbent body of the used sanitary product can be expanded, the treatment time of the pretreatment step S11, that is, the time for immersing the used sanitary product in warm water is not particularly limited, and is, for example, 2 minutes to 60 minutes, preferably 4 minutes to 30 minutes. If the time is too short, the absorbent body cannot be fully expanded, and if the time is too long, time is wasted, which unnecessarily increases the treatment cost.

[0095] In addition, as long as the absorbent body can expand to the extent that the used sanitary products can be decomposed in the decomposition step described later, the amount of warm water absorbed by the absorbent body in the pre-treatment step S11 is not particularly limited, and can be, for example, 80% by mass or more of the maximum absorption amount of the used sanitary products, preferably 90% by mass or more. In this way, the used sanitary products can be made to expand to the maximum extent by water. As a result, extremely high internal pressure can be generated in the absorbent body of the used sanitary products.

[0096] The maximum absorption amount was measured according to the following procedure.

[0097] (1) An unused sanitary product is dried in an atmosphere at 100° C. or higher, and the mass of the sanitary product is measured.

[0098] (2) When the sanitary product is provided with a stretchable material (e.g., a stretchable member around the leg or waist) that can form a pocket that makes it difficult for water to reach the absorbent body, the sanitary product is flattened by cutting a notch in the stretchable member.

[0099] (3) Immerse the sanitary article in a water bath filled with sufficient tap water with the liquid-permeable sheet facing downward, and leave it for 30 minutes.

[0100] (4) After the placement, the sanitary product was placed on a net with the liquid-permeable sheet facing downward, and the mass of the sanitary product was measured after the water was drained for 20 minutes.

[0101] Then, the difference in mass before and after immersion in tap water was defined as the maximum absorption amount.

[0102] Next, in the decomposition step S12, a physical impact is applied to the multiple used sanitary products that have been expanded and swollen in the pretreatment step S11, and the multiple used sanitary products are decomposed into a film (non-liquid-permeable sheet), a non-woven fabric (liquid-permeable sheet), a core wrap and an absorbent core (for example, an absorbent body and a superabsorbent polymer).

[0103] The used sanitary product is unfolded and flattened by the pre-treatment step S11, and any part of the surface is about to be broken due to the expansion. In this embodiment, the bonding force of the adhesive is reduced under the heat of warm water. Therefore, in the decomposition step S12, a physical impact is applied to the used sanitary product in this state, so that the bonding part of the liquid-permeable sheet (nonwoven fabric) and the liquid-impermeable sheet (film) in any part of the surface, especially the bonding force is reduced, is broken. In this way, the bonding part can be cracked (peeled off). There is no particular limitation on the physical impact, and examples thereof include a method of dropping the used sanitary product on a surface made of a raw material harder than the used sanitary product, a method of passing the used sanitary product between a pair of rollers arranged facing each other and pressing from both sides, etc.

[0104] In the present embodiment, the decomposition step S12 includes the following steps: a step of putting a plurality of swollen used sanitary products into the bottom of a rotating drum with a horizontal rotating axis; and a step of rotating the rotating drum around the rotating axis, thereby lifting a plurality of used sanitary products to the upper part of the rotating drum and smashing them at the bottom. Thus, physical impact can be applied stably, continuously (continuously) and easily to a plurality of used sanitary products. As a rotating drum, for example, a rotating drum of a washing tank of a horizontal washing machine can be listed, so the decomposition step S12 can be implemented using an existing horizontal washing machine (for example, ECO-22B manufactured by Inamoto Seisakusho Co., Ltd.). As long as the above-mentioned impact can be achieved, there is no particular restriction on the size of the rotating drum, and the inner diameter and depth can be listed, for example, 50 cm to 150 cm and 30 cm to 120 cm. As long as the above-mentioned impact can be achieved, there is no particular restriction on the rotation speed of the rotating drum, and for example, 30 times / minute to 100 times / minute can be listed.

[0105] In addition, the temperature of the used sanitary products is maintained at a relatively high temperature under the effect of the warm water absorbed into the used sanitary products. From the perspective of suppressing the temperature drop of the adhesive and maintaining the sterilization effect, the temperature of the atmosphere in the rotating drum is preferably 70°C or higher, more preferably 75°C or higher. From the perspective of handling the used sanitary products, the temperature in the rotating drum is preferably 98°C or lower, more preferably 90°C or lower. The water in the rotating drum is preferably as little as possible, at least preferably to the extent that the used sanitary products at the bottom are not under the water surface. If the used sanitary products are under the water surface, the impact applied to the used sanitary products will be absorbed by the water, and it is difficult to apply the desired impact to the used sanitary products. As long as it can be decomposed into the liquid-permeable sheet, the liquid-impermeable sheet, the core wrapping body, etc. and the absorbent core, the time for rotating the rotating drum is not particularly limited, for example, 2 minutes to 40 minutes, preferably 4 minutes to 20 minutes.

[0106] Under the action of physical impact, the joint part of the liquid-permeable sheet (nonwoven fabric) and the liquid-impermeable sheet (film) of the used sanitary product is broken and cracked. At the same time, under the action of the internal pressure of the absorbent body, the absorbent core (for example, pulp fibers and super absorbent polymer) in the used sanitary product is ejected (flies out) through the crack. In this way, the used sanitary product can be more reliably decomposed into the liquid-permeable sheet (nonwoven fabric), the liquid-impermeable sheet (film), the core wrapping body, etc., and the absorbent core (for example, pulp fiber containing material containing pulp fibers and super absorbent polymer).

[0107] Next, in the separation step S13, a plurality of films (impermeable sheets), a plurality of nonwoven fabrics (permeable sheets), a core wrapper, etc. are separated from the absorbent core (e.g., pulp fibers and superabsorbent polymer). The nonwoven fabric may be bonded to the film. The separation method is not particularly limited, and examples thereof include a method of using a sieve that does not allow the permeable sheet, the impermeable sheet, the core wrapper, etc. to pass but allows the absorbent core to pass.

[0108] In this embodiment, the separation step S13 may also include the following steps: an inactivation step S31, in which the super absorbent polymer is inactivated using an aqueous solution containing an inactivator before the film, non-woven fabric, core wrap, etc. are separated from the absorbent core; and a first separation step S32, in which the film and non-woven fabric are separated from a mixture containing pulp fibers, the inactivated super absorbent polymer, and wastewater discharged from the super absorbent polymer by inactivation.

[0109] In the inactivation step S31, before the first separation step S32, the liquid-permeable sheet (nonwoven fabric), the liquid-impermeable sheet (film), and the absorbent (pulp fibers and super absorbent polymer) are immersed in an aqueous solution containing an inactivating agent capable of inactivating the super absorbent polymer. Thus, the super absorbent polymer attached to the liquid-permeable sheet, the liquid-impermeable sheet, and the pulp fibers can be inactivated. Thus, the super absorbent polymer in a state of high viscosity before inactivation can be converted into a super absorbent polymer in a state of low viscosity by dehydration achieved by inactivation.

[0110] Here, the inactivating agent is not particularly limited, and examples thereof include acids (such as inorganic acids and organic acids), lime, calcium chloride, magnesium sulfate, magnesium chloride, aluminum sulfate, aluminum chloride, etc. The above acids are preferred because they do not leave ash residues in the pulp fibers. When an acid is used as an inactivating agent, the pH is preferably below 2.5, and more preferably 1.3 to 2.4. If the pH is too high, the water absorption capacity of the superabsorbent polymer cannot be sufficiently reduced. In addition, the bactericidal ability may also be reduced. If the pH is too low, the equipment may be corroded, and a large amount of alkaline chemicals may be required for the neutralization treatment during drainage treatment.

[0111] As the above-mentioned inorganic acid, for example, sulfuric acid, hydrochloric acid, and nitric acid can be listed, but sulfuric acid is preferred from the viewpoints of not containing chlorine and cost. On the other hand, as the above-mentioned organic acid, citric acid, tartaric acid, glycolic acid, malic acid, succinic acid, acetic acid, ascorbic acid, etc. can be listed, and particularly preferred are acids that can form complexes with metal ions contained in excreta, such as hydroxycarbonate organic acids such as citric acid, tartaric acid, and gluconic acid. It should be noted that as metal ions contained in excreta, calcium ions can be listed. This is because, under the action of the chelating effect of the acid that can form complexes with the metal ions contained in excreta, the metal ions in the excreta can be captured and removed. In addition, under the action of the cleaning effect of citric acid, a higher dirt component removal effect can be expected.

[0112] In addition, since pH changes depending on water temperature, pH in the present disclosure means pH measured under the condition of an aqueous solution temperature of 20°C.

[0113] As long as the inactivation reaction can proceed, the treatment temperature of the inactivation step S31, that is, the temperature of the aqueous solution containing the inactivating agent, is not particularly limited. The treatment temperature may be room temperature or higher than room temperature, and for example, 15°C to 30°C may be cited. In addition, as long as the highly water-absorbent polymer can be inactivated and dehydrated, the treatment time of the inactivation step S31, that is, the time for immersing the liquid-permeable sheet, the liquid-impermeable sheet and the absorbent body in the aqueous solution containing the inactivating agent, is not particularly limited, and for example, 2 minutes to 60 minutes may be cited, preferably 5 minutes to 30 minutes. In addition, as long as the inactivation reaction can proceed, the amount of the aqueous solution in the inactivation step S31, that is, the amount of the aqueous solution containing the inactivating agent, is not particularly limited. For example, the amount of the aqueous solution is preferably 300 to 3000 parts by mass, more preferably 500 to 2500 parts by mass, and further preferably 1000 to 2000 parts by mass, relative to 100 parts by mass of used sanitary products.

[0114] In the first separation step S32, the liquid-permeable sheet (nonwoven fabric), the liquid-impermeable sheet (film), and the core wrap are separated from the mixture containing pulp fibers, the inactivated super absorbent polymer, and the wastewater discharged from the super absorbent polymer by inactivation. The wastewater contains water released from the super absorbent polymer by dehydration using an aqueous solution containing an inactivating agent in the inactivation step S31, that is, liquid derived from excrement and water derived from warm water.

[0115] In the first separation step S32, the method for separating the liquid-permeable sheet and the liquid-impermeable sheet from the pulp fibers, the super absorbent polymer, and the sewage (the pulp fiber contents) is not particularly limited. For example, the products (liquid-permeable sheet, liquid-impermeable sheet, pulp fibers, super absorbent polymer, sewage, etc.) generated by the inactivation step are passed through a screen having a pore size of 5 mm to 100 mm, preferably a pore size of 10 mm to 60 mm, and discharged. Thus, the pulp fibers, super absorbent polymer, and sewage are left in the drainage and the liquid-permeable sheet and the liquid-impermeable sheet are left on the screen, so that the above products can be separated. It should be noted that other large-shaped objects such as nonwoven fabrics and films may also be left on the screen. In particular, before inactivation, since the super absorbent polymer is in a state of high viscosity, it is not so easy to separate the super absorbent polymer attached to the liquid-permeable sheet, the liquid-impermeable sheet, and the pulp fibers. However, after being inactivated, the super absorbent polymer becomes in a state of low viscosity due to dehydration, so the super absorbent polymer adhering to the liquid-permeable sheet, the liquid-impermeable sheet, and the pulp fibers can be easily separated from the liquid-permeable sheet, the liquid-impermeable sheet, and the pulp fibers. Therefore, the components of the sanitary product can be effectively separated and recovered.

[0116] In this embodiment, the separation step S13 may also include a second separation step S33, in which the adhesive at the joint portion between the film and other components is removed by using a solvent that can dissolve the adhesive at the joint portion. In this embodiment, the adhesive at each joint portion of the film, nonwoven fabric, and absorbent is removed by using a solvent that dissolves the adhesive at each joint portion.

[0117] In the second separation step S33, the adhesive at the joint between the film (impermeable sheet) and other components (nonwoven fabric of the liquid-permeable sheet, absorbent remaining on the surface of the liquid-permeable sheet, surface of the impermeable sheet, etc.) is removed by a solvent. As a result, the film and other components can be separated from each other in a manner that maintains their original shapes without breaking. Therefore, components such as the film of sanitary products can be effectively recycled. In addition, since the film and other components can be separated without leaving adhesive on the film, the film can be reused as a resin with higher purity. As a result, it is possible to suppress the situation where the adhesive has an adverse effect when the film is reused. The same is true for the nonwoven fabric and the film.

[0118] As long as the adhesive can be dissolved, the solvent used in the second separation step S33 is not particularly limited, and examples thereof include terpenes containing at least one of terpene hydrocarbons, terpene aldehydes, and terpene ketones. In this step, an aqueous solution containing terpene can be used, and the concentration of terpene in the aqueous solution can be, for example, 0.05 mass % or more and 2 mass % or less. Preferably, it is 0.075 mass % to 1 mass %. If the concentration of terpene is too low, the adhesive of the joint part may not be dissolved. If the concentration of terpene is too high, there is a problem of high cost. In addition, terpene can not only dissolve adhesives such as hot melt adhesives, but also has the effect of cleaning oil stains. Therefore, for example, in the case where the components of sanitary products such as non-liquid-permeable sheets have printed materials, terpene can also decompose and remove the printing ink.

[0119] As terpene hydrocarbons, for example, myrcene, limonene, pinene, camphor, sabinene, phellandrene, para-cymene, ocimene, terpinene, carene, gingerene, caryophyllene, bisabolene, and cedrene can be cited. Among them, limonene, pinene, terpinene, and carene are preferred. In addition, as terpene aldehydes, for example, citronellal, citral, cyclocitral, safranal, celery aldehyde, perillaldehyde, geranial, and neral can be cited. As terpene ketones, for example, camphor and thuja ketone can be cited. Among terpenes, terpene hydrocarbons are preferred, and limonene is particularly preferred. Limonene includes d-limonene, l-limonene, and dipentene (dl-limonene), all of which can be preferably used. For terpenes, one type can be used alone, or two or more types can be used in combination.

[0120] As long as the dissolution of the adhesive can progress and the used sanitary products can be decomposed into components, the treatment temperature of the second separation step S33, that is, the temperature of the aqueous solution containing the solvent, is not particularly limited. The treatment temperature may be room temperature or higher than room temperature, and for example, 15°C to 30°C can be cited. In addition, as long as the dissolution of the adhesive can progress and the used sanitary products can be decomposed into components, the treatment time of the second separation step S33, that is, the time for immersing the liquid-permeable sheet, the liquid-impermeable sheet and the absorbent body in the aqueous solution containing the solvent, is not particularly limited. The treatment time can be cited, for example, from 2 minutes to 60 minutes, preferably from 5 minutes to 30 minutes. As long as the dissolution of the adhesive can progress and the used sanitary products can be decomposed into components, the amount of the aqueous solution in the second separation step S33, that is, the amount of the aqueous solution containing the solvent, is not particularly limited. For example, the amount of the aqueous solution is preferably 300 parts by mass to 3000 parts by mass, and more preferably 500 parts by mass to 2500 parts by mass, relative to 100 parts by mass of the used sanitary products. By the second separation step S33, the amount of the adhesive remaining in the film, nonwoven fabric, absorbent body, etc. can be reduced to 1% by mass or less relative to the film, nonwoven fabric, absorbent body, etc.

[0121] It should be noted that in this embodiment, as another mode, the second separation step S33 may be performed simultaneously in the inactivation step S31. That is, the adhesive attached to the liquid-permeable sheet, the liquid-impermeable sheet, and the pulp fibers may be dissolved while the superabsorbent polymer attached to the liquid-permeable sheet, the liquid-impermeable sheet, and the pulp fibers is inactivated. In this case, an aqueous solution containing both an inactivator and a solvent is used as an aqueous solution for impregnating the liquid-permeable sheet, the liquid-impermeable sheet, the pulp fibers, and the superabsorbent polymer. Thus, in the inactivation step S31, a state in which the liquid-impermeable sheet (film), the liquid-permeable sheet (nonwoven fabric), and the absorbent (pulp fibers and superabsorbent polymer) are roughly separated in the aqueous solution can be formed. Moreover, in the subsequent first separation step, the liquid-impermeable sheet (film) and the liquid-permeable sheet (nonwoven fabric) can be separated from the absorbent (pulp fibers and superabsorbent polymer), and the second separation step S33 can be omitted. In this case, the liquid-impermeable sheet (film) and the liquid-permeable sheet (nonwoven fabric) are substantially separated by removing the adhesive.

[0122] In this embodiment, the separation step S13 may further include a first drying step S34 of drying the film with an atmosphere at a temperature higher than room temperature or hot air to remove the solvent after removing the adhesive from the bonded portion. In this embodiment, the nonwoven fabric is also dried in this step.

[0123] In the process of reusing used sanitary products, sterilization is extremely important. In the first drying step S34, a process of drying the separated film (non-liquid-permeable sheet) and non-woven fabric (liquid-permeable sheet) using a high-temperature atmosphere or hot air is performed. The drying temperature can be, for example, 105°C to 210°C, preferably 110°C to 190°C. The drying time also depends on the drying temperature, and can be, for example, 10 minutes to 120 minutes, preferably 15 minutes to 100 minutes. In this way, not only can the solvent remaining on the surface of the film and the surface of the non-woven fabric be evaporated and removed, but the film and non-woven fabric can also be sterilized using a high-temperature atmosphere or hot air. In this way, while removing the solvent, it can also have a sterilization (disinfection) effect.

[0124] On the other hand, in the present embodiment, the separation step S13 may also include a third separation step S35 for separating pulp fibers from the separated mixture. In the third separation step S35, there is no particular limitation on the method for separating pulp fibers from the separated mixture (containing pulp fibers, super absorbent polymers, and sewage). For example, the separated mixture is passed through a sieve having a pore size of 0.1 mm to 4 mm, preferably a pore size of 0.15 mm to 2 mm, and discharged. Thus, the super absorbent polymer and sewage are left in the drainage, and the pulp fibers (mainly the super absorbent polymer remaining on the surface) are left on the sieve, so that the pulp fibers can be separated from the mixture. The pulp fibers contain a large amount of impurities, but can be reused in this state depending on the purpose.

[0125] The separated pulp fibers have a highly absorbent polymer attached to them, and the separated pulp fibers, the highly absorbent polymer attached to the pulp fibers, and water are mixed at a predetermined ratio and enter the ozone treatment step S36 as a pulp fiber-containing material.

[0126] In this embodiment, the separation step S13 includes an ozone treatment step S36, in which the pulp fiber content including the highly absorbent polymer, pulp fibers, their connecting structures, and water is treated with an aqueous solution containing ozone, and the highly absorbent polymer attached to the pulp fibers is reduced in molecular weight and dissolved to be removed.

[0127] In used sanitary products, absorbents containing pulp fibers and super absorbent polymers often form a connected structure of multiple super absorbent polymers and multiple pulp fibers for the following reasons: (i) the super absorbent polymers enlarge as they absorb body fluids and other liquids, and thus become entangled in the pulp fibers; (ii) the enlarged super absorbent polymers become gelled while being entangled in the pulp fibers. In the pulp fiber-containing material, in addition to free pulp fibers and free super absorbent polymers, the connected structure of multiple super absorbent polymers and multiple pulp fibers is also contained.

[0128] In the ozone treatment step S36, the highly water-absorbent polymer contained in the pulp fiber content (treatment liquid) is oxidatively decomposed by the ozone in the aqueous solution to make it soluble in the aqueous solution, thereby removing the highly water-absorbent polymer.

[0129] The state where the super absorbent polymer is oxidatively decomposed and made soluble in an aqueous solution means that the super absorbent polymer and the linked structure pass through a 2 mm sieve. In this way, impurities such as the super absorbent polymer can be removed from the pulp fiber content (treatment liquid) to produce pulp fibers with higher purity. In addition, the pulp fibers can be secondary sterilized, bleached and deodorized by ozone treatment.

[0130] Figure 2 1 is a schematic diagram showing an example of the structure of the apparatus 2 for performing the ozone treatment step S36. The apparatus 2 includes: a pulp fiber content storage section 3 for storing a pulp fiber content 51 including water, a highly absorbent polymer, and the pulp fibers separated in the third separation step S35; and an ozone treatment section 4 for oxidatively decomposing the highly absorbent polymer contained in the pulp fiber content 51 to remove it from the pulp fibers.

[0131] The pulp fiber content storage section 3 includes a pulp fiber content tank 12 and a stirrer 13. The pulp fiber content tank 12 stores the pulp fiber content 51 supplied via the pipe 61. The stirrer 13 stirs the pulp fiber content 51 in the pulp fiber content tank 12 to prevent the pulp fibers and the highly absorbent polymer in the pulp fiber content 51 from being separated from the water and sinking to the bottom of the pulp fiber content 51.

[0132] On the other hand, the ozone treatment section 4 includes a supply pump 21, a treatment tank 31, an ozone supply device 41, a delivery pump 22, and an ozone decomposition device 34. The treatment tank 31 has an acidic aqueous solution as a treatment liquid 52. The treatment tank 31 includes a pulp fiber content supply port 32, a treatment liquid discharge port 33, and an ozone-containing gas supply port 43. The pulp fiber content supply port 32 is arranged at the upper part of the treatment tank 31, and is used to supply the pulp fiber content 51 to the treatment tank 31. The treatment liquid discharge port 33 is arranged at the lower part of the treatment tank 31, and is used to discharge the treatment liquid 52. The ozone-containing gas supply port 43 is arranged at the lower part of the treatment tank 31, specifically, closer to the upper part than the treatment liquid discharge port 33, and is used to deliver the ozone-containing gas 53 into the treatment tank 31.

[0133] Specifically, the supply pump 21 continuously supplies the pulp fiber content 51 of the pulp fiber content tank 12 from the pulp fiber content supply port 32 to the treatment tank 31 at a first flow rate via the piping 62. The ozone supply device 41 is used to supply an ozone-containing gas 53 to the treatment tank 31. As for the ozone generating device 42 of the ozone supply device 41, for example, an ozone water exposure tester ED-OWX-2 manufactured by Ecodesign Co., Ltd., an ozone generating device OS-25V manufactured by Mitsubishi Electric Corporation, etc. can be listed. The ozone-containing gas 53 is other types of gas including ozone, and for example, oxygen containing ozone can be listed. The ozone-containing gas supply port 43 is used to deliver the ozone-containing gas 53 supplied to the treatment tank 31 via the piping 65 into the treatment tank 31, and it is arranged at the lower part (preferably the bottom) of the treatment tank 31. The ozone-containing gas supply port 43 continuously supplies the ozone-containing gas 53 in the form of a plurality of fine bubbles from the lower part of the treatment liquid 52 (treatment tank 31) toward the upper part. The delivery pump 22 continuously discharges the treatment liquid 52 in the treatment tank 31 from the treatment liquid discharge port 33 to the outside of the treatment tank 31 at a second flow rate through the pipe 63. The ozone decomposition device 34 receives the ozone-containing gas 53 accumulated in the upper part of the treatment tank 31 through the pipe 64, and releases it to the outside after detoxifying the ozone. It should be noted that, with respect to the treatment liquid 52 in the treatment tank 31, before the start of the ozone treatment process S36, it is only the treatment liquid 52, and after the start of the ozone treatment process S36, it becomes a liquid formed by a mixture of the treatment liquid 52 and the pulp fiber content 51. However, in the present embodiment, the liquid in the treatment tank 31 includes the liquid formed by a mixture of the treatment liquid 52 and the pulp fiber content 51, and all the liquid in the treatment tank 31 is recorded as the treatment liquid 52.

[0134] Next, a specific method of the ozone treatment step S36 will be described.

[0135] The pulp fibers and the highly absorbent polymer separated in the third separation step S35 are mixed with water in a manner to achieve a predetermined concentration, thereby forming a pulp fiber content 51. The concentration of the pulp fibers in the pulp fiber content 51 is set to a value such that the pulp fibers become the predetermined concentration when they are put into the treatment tank 31 and mixed with the treatment liquid 52. The pulp fiber content 51 is supplied to and stored in the pulp fiber content tank 12 via the pipe 61. Since the specific gravity of the pulp fibers and the highly absorbent polymer is greater than 1, the pulp fiber content 51 is stirred in the pulp fiber content tank 12 by the stirrer 13 in order to prevent the pulp fibers and the highly absorbent polymer from being separated from the water.

[0136] Then, the flow rate of the pulp fiber content 51 in the pulp fiber content tank 12 is controlled by the supply pump 21, and the pulp fiber content 51 in the pulp fiber content tank 12 is continuously supplied to the treatment tank 31 from the pulp fiber content supply port 32 at a first flow rate through the pipe 62. The treatment liquid 52 is an acidic aqueous solution with a specific gravity of about 1. Therefore, the pulp fibers and the highly absorbent polymer settle from the upper part of the treatment liquid 52 to the lower part.

[0137] On the other hand, the ozone-containing gas 53 generated by the ozone generator 42 is supplied to the treatment tank 31 through the pipe 65, and the ozone-containing gas 53 is discharged into the treatment liquid 52 from the ozone-containing gas supply port 43 of the treatment tank 31 in the form of fine bubbles (e.g., microbubbles or nanobubbles). That is, the ozone-containing gas 53 is made to rise from the lower part of the treatment liquid 52 to the upper part.

[0138] Then, the pulp fibers and the super absorbent polymer moving downward, i.e., descending, and the ozone-containing gas 53 moving upward, i.e., ascending, in the treatment liquid 52 move relative to each other and collide with each other. Then, the ozone-containing gas 53 adheres to the surfaces of the pulp fibers, the super absorbent polymer, and the connecting structure. The ozone in the ozone-containing gas 53 oxidatively decomposes the free super absorbent polymer and dissolves it in the treatment liquid 52. Thus, the super absorbent polymer on the pulp fibers is removed from the pulp fibers. Then, the pulp fibers descend to the bottom of the treatment tank 31, and the ozone-containing gas 53 ascends to the upper space of the treatment tank 31.

[0139] Among the free super absorbent polymer, free pulp fibers, and interconnected structures, the free super absorbent polymer having relatively low buoyancy and the interconnected structures containing the super absorbent polymer tend to have higher sedimentation properties than the free pulp fibers having relatively high buoyancy. On the other hand, since the ozone-containing gas rises while treating the super absorbent polymer and pulp fibers in a manner that consumes ozone, the ozone-containing gas present at a lower position tends to have a higher ozone content (i.e., fresher) than the ozone-containing gas present at an upper position.

[0140] Therefore, the free super absorbent polymer and the linking structure that move downward relatively quickly can be properly oxidized and decomposed by fresher ozone-containing gas, thereby forming free pulp fibers. On the other hand, since the free pulp fibers move downward relatively slowly, the ozone-containing gas can take time to process the free pulp fibers. Specifically, the ozone in the ozone-containing gas can decompose the hemicellulose, lignin, etc. of the pulp fibers by being opposite to and colliding with the pulp fibers.

[0141] After that, the treated liquid 52 (containing pulp fiber raw material) at the bottom of the treatment tank 31 is continuously discharged from the treated liquid discharge port 33 of the treatment tank 31 to the outside of the treatment tank 31 through the pipe 63 at a second flow rate by controlling the flow rate of the delivery pump 22. The ozone containing gas 53 accumulated in the upper part of the treatment tank 31 is rendered harmless by the ozone decomposition device 34 and then released to the outside.

[0142] In this way, the pulp fiber content 51 is continuously supplied to the processing tank 31 from the upper part of the processing tank 31 at a first flow rate, and the treatment liquid 52 is continuously discharged from the lower part (bottom) of the processing tank 31 to the outside of the processing tank 31 at a second flow rate. In this way, a continuous and stable flow of a fluid (including pulp fiber raw material) from the upper part to the lower part can be forcibly generated in the processing tank 31.

[0143] The treated liquid 52 discharged from the treatment tank 31 contains the pulp fiber raw material from which the super absorbent polymer, hemicellulose, lignin, etc. are removed, and contains low molecular weight organic matter generated by oxidative decomposition of the super absorbent polymer. The pulp fiber raw material is recovered in a process on the downstream side of the delivery pump 22, for example, in the fourth separation process S37 described later.

[0144] In the present method, a pulp fiber content 51 containing at least pulp fibers and a super absorbent polymer is continuously supplied at a first flow rate to a treatment tank 31 having a treatment liquid 52 capable of dissolving the super absorbent polymer, and the treatment liquid 52 containing the pulp fiber raw material from which the super absorbent polymer has been removed and containing low molecular weight organic matter generated by oxidative decomposition of the super absorbent polymer is continuously discharged out of the treatment tank 31 at a second flow rate. With such a structure, a continuous and stable flow of a fluid (containing pulp fibers) can be forcibly generated from the pulp fiber content supply port 32 of the treatment tank 31 for supplying the pulp fiber content 51 toward the treatment liquid discharge port 33 for discharging the treatment liquid 52. Under the action of the flow of the fluid, i.e., the water flow, even if the treatment amount of the pulp fibers and the super absorbent polymer is large, the super absorbent polymer can be treated (made solubilized) and the pulp fibers can be treated.

[0145] Here, the first flow rate and the second flow rate are preferably the same. By making the first flow rate and the second flow rate the same, the amount of the treatment liquid 52 in the treatment tank 31 can be kept constant, and stable and continuous processing can be performed. However, if the amount of the treatment liquid 52 in the treatment tank 31 can be kept approximately constant, that is, the amount of the treatment liquid 52 in the treatment tank 31 will not increase or decrease significantly, the first flow rate and the second flow rate can also change over time. That is, the first flow rate and the second flow rate do not have to be exactly the same all the time, as long as they are approximately the same on average over time. Here, approximately the same means that the difference between the first flow rate and the second flow rate is within 5 mass %. In this case, stable and continuous processing can also be performed.

[0146] When the ozone-containing gas 53 is supplied to the treatment liquid 52, the ozone concentration in the treatment liquid 52 is not particularly limited as long as it is a concentration that can oxidatively decompose the super absorbent polymer, and examples thereof include 1 mass ppm to 50 mass ppm, preferably 2 mass ppm to 40 mass ppm, and more preferably 3 mass ppm to 30 mass ppm. If the ozone concentration in the treatment liquid 52 is too low, the super absorbent polymer cannot be completely dissolved, and the super absorbent polymer may remain in the pulp fiber. On the contrary, if the ozone concentration in the treatment liquid 52 is too high, the oxidizing power is also increased, so that the pulp fiber may be damaged, and there may also be problems in safety. The ozone treatment temperature is not particularly limited as long as it is a temperature that can oxidatively decompose the super absorbent polymer, and for example, it may be room temperature or higher than room temperature.

[0147] The ozone concentration in the treatment liquid 52 (aqueous solution) was measured by the following method.

[0148] (1) Into a 100-mL measuring cylinder containing about 0.15 g of potassium iodide and 5 mL of a 10% citric acid solution, 85 mL of the treatment solution 52 in which ozone is dissolved is added to carry out a reaction.

[0149] (2) The treated liquid 52 after the reaction was transferred to a 200 mL conical flask. After adding the starch solution to the conical flask to color it purple, it was titrated with 0.01 mol / L sodium thiosulfate while stirring until it became colorless. The added amount a (mL) was recorded.

[0150] (3) The ozone concentration in the aqueous solution was calculated using the following formula.

[0151] The ozone concentration (mass ppm) in the aqueous solution was calculated using the following formula:

[0152] Ozone concentration in aqueous solution (mass ppm) = a (mL) × 0.24 × 0.85 (mL)

[0153] The ozone concentration in the ozone-containing gas 53 is preferably 40 g / m 3 ~200g / m 3 , more preferably 80g / m 3 ~200g / m 3 , more preferably 100g / m 3 ~200g / m 3 . If the ozone concentration in the ozone-containing gas 53 is too low, the super absorbent polymer cannot be completely solubilized, and the super absorbent polymer may remain. If the concentration in the ozone-containing gas 53 is too high, it may cause damage to the pulp fibers, reduce safety, and increase manufacturing costs. It should be noted that the ozone concentration in the ozone-containing gas 53 can be measured using, for example, an ultraviolet absorption ozone concentration meter (for example, the ozone monitor OZM-5000G manufactured by Eco design Co., Ltd.).

[0154] The concentration of the pulp fiber content (e.g., pulp fiber and super absorbent polymer) in the treatment liquid 52 is not particularly limited as long as it is a concentration in the treatment liquid 52 that can oxidatively decompose the super absorbent polymer by ozone, and can be, for example, 0.1% to 20% by mass, preferably 0.2% to 10% by mass, and more preferably 0.3% to 5% by mass. If the concentration of the pulp fiber is too high, the super absorbent polymer cannot be completely dissolved, and the super absorbent polymer may remain in the pulp fiber. On the contrary, if the concentration of the pulp fiber is too low, the oxidizing ability will also increase, so that the pulp fiber may be damaged, and there may also be problems in safety. The concentration of the pulp fiber and the concentration of the super absorbent polymer in the pulp fiber content 51 are appropriately set according to the concentration of the pulp fiber and the concentration of the super absorbent polymer in the treatment liquid 52 and the amount of the treatment liquid 52.

[0155] When ozone is supplied to the treatment liquid 52 containing pulp fibers and super absorbent polymers, the treatment liquid 52 is preferably acidic (specifically, exceeding pH 0.0 and less than pH 3.0, preferably greater than pH 2.5 and less than pH 3.0), weakly acidic (specifically, greater than pH 3.0 and less than pH 6.0), or neutral (specifically, greater than pH 6.0 and less than pH 8.0, preferably greater than pH 6.0 and less than pH 7.0). More preferably, the pH of the treatment liquid 52 exceeds 0.0 and is less than pH 7.0, and further preferably is 2.5 to 6.0. By treating in an acidic state, the deactivation of ozone is suppressed, and the oxidative decomposition effect of ozone on super absorbent polymers is improved, so that the super absorbent polymers can be oxidatively decomposed in a short time. In order to maintain the pH of the treatment liquid, the pH of the pulp fiber content 51 can also be made the same as the pH of the treatment liquid 52, so that the pulp fiber content 51 is supplied to the treatment tank 31. Alternatively, the pH of the treatment liquid 52 may be monitored by a pH sensor, and when the pH changes to the neutral side, only a predetermined acidic solution in an amount corresponding to the change range may be added to the treatment liquid 52 .

[0156] The amount of the treatment liquid 52 (containing the pulp fiber content 51) in the treatment tank 31 is not particularly limited as long as it is an amount that can oxidatively decompose the super absorbent polymer. The volume V (unit: L) of the treatment liquid 52 in the treatment tank 31 and the mass W (unit: kg) of the pulp fiber preferably satisfy 30≤V / W≤1000. It is more preferably 50≤V / W≤400, and further preferably 100≤V / W≤200. If V / W is too small, the super absorbent polymer cannot be completely dissolved, and the super absorbent polymer may remain. If V / W is too large, it may lead to an increase in manufacturing costs. It should be noted that the volume V of the treatment tank 31 is not particularly limited, and for example, 50L to 80L can be listed.

[0157] Ozone-containing gas flow rate R O (unit: L / min) and the volume V (unit: L) of the treatment liquid 52 in the treatment tank 31 preferably satisfy 0.01≤R O / V≤1.25. More preferably, 0.03≤R O / V≤1.0, more preferably 0.06≤R O / V≤0.75. If R O If R / V is too small, the super absorbent polymer cannot be completely solubilized, and there is a possibility that the super absorbent polymer will remain in the pulp fiber. O If / V is too large, it may cause damage to pulp fibers, reduce safety, and increase manufacturing costs. O There are no particular limitations, but examples thereof include 3 L / min to 6 L / min.

[0158] The time during which the pulp fiber content exists in the treatment tank 31, that is, the time during which the pulp fiber content is treated in the treatment liquid 52 (hereinafter also referred to as "tank treatment time") varies depending on the purpose of decomposing hemicellulose in the pulp fiber, decomposing lignin, oxidative decomposition of the super absorbent polymer, etc., and is not particularly limited. If the ozone concentration of the treatment liquid 52 is high, the tank treatment time can be shorter, and if the ozone concentration of the treatment liquid 52 is low, a longer tank treatment time is required. The tank treatment time can be, for example, 15 minutes to 180 minutes, preferably 30 minutes to 60 minutes.

[0159] The ozone concentration (g / m 3 The ozone-containing gas and the pulp fiber content are contacted by adjusting the CT value of the product of the treatment time (in minutes) and the tank. The CT value is preferably 6000 g / m 3 · Minutes or more, more preferably 7000g / m 3 · Minutes or more, more preferably 8000g / m 3 · minutes or more, and further preferably 9000 g / m 3 Minutes or more.

[0160] The above CT value is preferably 12000g / m 3 Less than 10 minutes, more preferably 11000 g / m 3 Minutes or less, more preferably 10000g / m 3 · minutes or less, and further preferably 9000 g / m 3 Less than minutes.

[0161] When the CT value is within the above range, it is easy to form a pulp fiber raw material having a predetermined hemicellulose content. It should be noted that if the above CT value is too small, the decomposition of hemicellulose, the decomposition of lignin, the decomposition of super absorbent polymer, and especially the decomposition of hemicellulose may be insufficient. If the above CT value is too large, it may cause damage to the pulp fiber, reduce safety, and increase manufacturing costs.

[0162] In addition, the method of measuring the ozone concentration in the ozone-containing gas in the CT value is as described above.

[0163] In addition, the tank treatment time in the CT value refers to the time (minutes) for supplying ozone-containing gas in the case of the so-called batch method. In the case of the so-called continuous method, the tank treatment time refers to the value obtained by dividing the volume (L) of the treatment liquid in the treatment tank by the discharge volume per unit time (L / minute).

[0164] While the pulp fibers are present in the treatment tank 31, the highly absorbent polymer is oxidatively decomposed into low molecular weight components by ozone and dissolved in the treatment liquid 52. In addition, the hemicellulose in the pulp fibers is decomposed by ozone and part of it is dissolved in the treatment liquid 52. In addition, the lignin in the pulp fibers is decomposed by ozone and dissolved in the treatment liquid 52. The low molecular weight components of the highly absorbent polymer, the decomposition products of hemicellulose, the decomposition products of lignin, etc. dissolved in the treatment liquid 52 are discharged together with the treatment liquid 52. In addition, in this process, the used sanitary products are sterilized once by the sterilization effect of ozone. As described above, the pulp fiber raw material is formed.

[0165] The method for producing pulp fiber raw material disclosed herein includes the following steps.

[0166] A pulp fiber raw material forming step of supplying ozone-containing gas to a treatment liquid containing the pulp fibers to be treated, thereby forming the pulp fiber raw material having a hemicellulose content of less than 8.0% by mass from the pulp fibers to be treated.

[0167] With regard to the step of forming the pulp fiber raw material, there are no particular restrictions as long as ozone-containing gas is supplied to a treatment liquid containing the pulp fibers to be treated to form a pulp fiber raw material having a hemicellulose content of less than 8.0% by mass from the pulp fibers to be treated. For example, it may be carried out in a so-called batch method, continuous method, or the like.

[0168] The treatment liquid contains at least the pulp fibers to be treated as pulp fiber contents, and may contain pulp fibers alone. In addition, when the pulp fibers to be treated are pulp fibers contained in used sanitary products, the treatment liquid may contain pulp fiber contents containing the pulp fibers to be treated and other components, such as pulp fibers and highly absorbent polymers. In addition, the treatment liquid may also contain, as pulp fiber contents, a connected structure obtained by connecting a plurality of highly absorbent polymers to a plurality of pulp fibers, materials constituting sanitary products (such as a core wrap, a liquid-permeable sheet, a liquid-impermeable sheet, etc.), etc.

[0169] The ozone-containing gas may be supplied, for example, into the treatment liquid in the treatment tank, or may be supplied into the space above the treatment liquid in the treatment tank.

[0170] The method for producing a pulp fiber raw material disclosed herein may include the following steps: a preparation step, a pulp fiber-containing material supply step, an ozone-containing gas supply step, a pulp fiber raw material forming step, and a treatment liquid discharge step.

[0171] A preparation step of preparing the treatment tank including a pulp fiber-containing material supply port, a treatment liquid discharge port disposed below the pulp fiber-containing material supply port, and an ozone-containing gas supply port.

[0172] A pulp fiber-containing material supplying step in which the pulp fiber-containing material is supplied from the pulp fiber-containing material supply port to the treatment tank.

[0173] An ozone-containing gas supplying step of supplying the ozone-containing gas from the ozone-containing gas supply port to the treatment liquid in the treatment tank.

[0174] A pulp fiber raw material forming step, in which the pulp fiber content is lowered while the ozone-containing gas is raised in the treatment tank, thereby bringing the pulp fiber content into contact with the ozone-containing gas to form the pulp fiber raw material from the pulp fibers to be treated.

[0175] A treatment liquid discharging step of discharging the treatment liquid containing the pulp fiber raw material from the treatment liquid discharging port.

[0176] Hemicellulose has a lower specific gravity than cellulose, so pulp fibers with a relatively low hemicellulose content (pulp fibers with a relatively high cellulose content) tend to have a relatively high specific gravity compared to pulp fibers with a relatively high hemicellulose content (pulp fibers with a relatively low cellulose content). On the other hand, in a solution, since ozone-containing gas rises while consuming ozone, ozone-containing gas present at a lower position tends to have a higher ozone content (i.e., fresher) than ozone-containing gas present at an upper position.

[0177] The manufacturing method comprises a predetermined preparation step, a pulp fiber content supply step, an ozone-containing gas supply step, a pulp fiber raw material forming step and a treatment liquid discharge step. In the pulp fiber raw material forming step, the pulp fiber content is brought into contact with the ozone-containing gas while the ozone-containing gas is raised.

[0178] In the above-mentioned manufacturing method, the pulp fiber to be treated with a relatively low hemicellulose content (the pulp fiber to be treated with a relatively high cellulose content) has a relatively high sedimentation property (or a relatively low floating property) compared with the pulp fiber to be treated with a relatively high hemicellulose content (the pulp fiber to be treated with a relatively low cellulose content), and the fresh ozone-containing gas contacts the pulp fiber to be treated with a relatively low hemicellulose content, and further easily decomposes the hemicellulose contained therein. Therefore, the above-mentioned manufacturing method can manufacture a pulp fiber raw material that can easily form a fiber composite reinforcement material containing cellulose nanofibers.

[0179] It should be noted that generally, the higher the lignin content of pulp fibers, the lower their specific gravity. Therefore, in the above-mentioned manufacturing method, the pulp fibers to be treated with a relatively low lignin content have a relatively high sedimentation property compared to the pulp fibers to be treated with a relatively high lignin content. Therefore, fresher ozone-containing gas comes into contact with the pulp fibers to be treated with a relatively high lignin content, which can further decompose the lignin contained therein.

[0180] The ozone-containing gas supply port is located at the bottom of the treatment tank, and specifically, is preferably located within a range of 30%, more preferably 20%, and even more preferably 10% of the height of the treatment tank from the bottom of the treatment tank.

[0181] In addition, the pulp fiber content supply port can be arranged below the ozone-containing gas supply port, or can be arranged above the ozone-containing gas supply port, and the treatment liquid discharge port can be arranged below the ozone-containing gas supply port, or can be arranged above the ozone-containing gas supply port.

[0182] It should be noted that the above-mentioned manufacturing method includes the so-called continuous and batch manufacturing methods. In addition, "raising the ozone-containing gas" means that the ozone-containing gas rises as a whole, and when the treatment liquid in the stirring treatment tank is stirred, the ozone-containing gas is stirred in the horizontal direction and rises in the vertical direction as a whole.

[0183] The above-mentioned treatment liquid discharge port is arranged below the above-mentioned pulp fiber content supply port, and in the above-mentioned pulp fiber raw material forming step, the above-mentioned pulp fiber content can be brought into contact with the above-mentioned ozone-containing gas while the above-mentioned pulp fiber content is lowered. As a result, the frequency of contact between the pulp fiber content and the ozone-containing gas increases, and the distribution of the hemicellulose content of the pulp fiber raw material contained in the treatment liquid becomes narrower (the deviation is reduced). In addition, the fresh ozone-containing gas can contact the pulp fiber to be treated with a relatively low hemicellulose content, so the hemicellulose content of the pulp fiber raw material contained in the treatment liquid is easily reduced. Furthermore, since the above-mentioned treatment liquid discharge port is arranged below the above-mentioned pulp fiber content supply port, the pulp fiber to be treated with a relatively low hemicellulose content (the pulp fiber to be treated with a relatively high cellulose content) is easily discharged from the treatment liquid discharge port.

[0184] It should be noted that the above-mentioned manufacturing method includes two manufacturing methods, namely, the so-called continuous method and the batch method. In addition, "lowering the pulp fiber content" means that at least a part of the pulp fiber content is lowered, for example, the entire treatment liquid in the treatment tank is lowered, the lowered part of the pulp fiber content when the treatment liquid in the treatment tank is convected up and down, etc.

[0185] The treatment liquid discharge port is arranged above the pulp fiber-containing material supply port, and the pulp fiber-containing material can be brought into contact with the ozone-containing gas while the pulp fiber-containing material is raised in the pulp fiber raw material forming step. Thus, the contact time between the pulp fiber-containing material and the ozone-containing gas is prolonged, and the hemicellulose content in the pulp fiber to be treated is easily reduced.

[0186] It should be noted that the above-mentioned manufacturing method includes two manufacturing methods, namely, the so-called continuous method and the batch method. In addition, "raising the pulp fiber content" means that at least a part of the pulp fiber content rises, for example, the whole when the treatment liquid in the treatment tank rises as a whole, the rising part of the pulp fiber content when the treatment liquid in the treatment tank is convected up and down, etc.

[0187] In the pulp fiber content supplying step, the pulp fiber content may be continuously supplied to the treatment tank from the pulp fiber content supply port at a first flow rate, and in the treatment liquid discharge step, the treatment liquid may be continuously discharged from the treatment liquid discharge port at a second flow rate. Thus, the treatment time of the pulp fiber content to be treated is uniformed, and the distribution of the hemicellulose content of the pulp fiber raw material contained in the treatment liquid is narrowed (the deviation is reduced).

[0188] When the used sanitary products contain a super absorbent polymer, the pulp fiber content in the pulp fiber content supplying step and the pulp fiber raw material forming step further contains the super absorbent polymer, and in the pulp fiber raw material forming step, at least a portion of the super absorbent polymer can be dissolved in the treatment liquid.

[0189] In used sanitary products, for absorbent bodies containing pulp fibers and super absorbent polymers, there are many cases where multiple super absorbent polymers and multiple pulp fibers form a connected structure for the following reasons: reason (i) the super absorbent polymer will enlarge as it absorbs liquids such as body fluids, thereby entangling the pulp fibers; reason (ii) the enlarged super absorbent polymers will entangling pulp fibers and forming gel lumps, etc.

[0190] In the pulp fiber raw material forming step, the ozone-containing gas is raised while the pulp fiber content is contacted with the ozone-containing gas. For free superabsorbent polymers and free pulp fibers, and linked structures, the free superabsorbent polymers and linked structures with relatively low buoyancy tend to have higher sedimentation than the free pulp fibers with relatively high buoyancy. On the other hand, since the ozone-containing gas rises while treating the pulp fiber content in an ozone-consuming manner, the ozone-containing gas at a lower position tends to have a higher ozone content (i.e., fresher) than the ozone-containing gas at an upper position.

[0191] Therefore, the free highly absorbent polymers with relatively high sedimentation properties and the highly absorbent polymers in the connecting structure can be properly oxidized and decomposed by fresher ozone-containing gas, so that the pulp fibers constituting the connecting structure can be freed, and the ozone-containing gas takes time to treat the free pulp fibers with relatively low sedimentation properties and takes relatively long time to reach the treatment liquid discharge outlet, so that the hemicellulose contained in the free pulp fibers can be decomposed.

[0192] In addition, as described above, pulp fibers with relatively low hemicellulose content (pulp fibers with relatively high cellulose content) have higher sedimentation properties than pulp fibers with relatively high hemicellulose content (pulp fibers with relatively low cellulose content). When the above-mentioned manufacturing method is used, fresher ozone-containing gas comes into contact with the pulp fibers with relatively low hemicellulose content, thereby further decomposing the hemicellulose contained therein.

[0193] Figure 1 In the illustrated embodiment, as one mode, the ozone treatment step S36 (continuous treatment step) includes a step of continuously supplying the pulp fiber content 51 from the upper part of the treatment tank 31 and continuously discharging the treatment liquid 52 from the lower part of the treatment tank 31. The pulp fibers and the super absorbent polymer in the pulp fiber content 51 have low buoyancy, and the pulp fibers, the super absorbent polymer, and the connecting structure naturally settle.

[0194] In the present embodiment, as one mode, the treatment liquid 52 capable of dissolving the super absorbent polymer is an aqueous solution containing ozone-containing gas that oxidatively decomposes the super absorbent polymer in a dissolving manner. The ozone treatment step S36 (continuous treatment step) also includes a sending step of continuously sending a plurality of bubbles of ozone-containing gas from the lower part of the treatment liquid 52 to the upper part. In one mode of such a method, in the treatment liquid 52, the ozone-containing gas rises and the pulp fibers and the super absorbent polymer fall, that is, a relative flow is formed. As a result, the probability of contact between the pulp fibers and the super absorbent polymer and the ozone-containing gas can be increased. In addition, the deeper the pulp fibers and the super absorbent polymer settle, the more likely they are to contact with the high-concentration ozone-containing gas. Therefore, the super absorbent polymer, hemicellulose, lignin, etc., which are not completely dissolved in the treatment liquid 52 only by the ozone-containing gas contacted at a shallower part in the treatment liquid 52, can be contacted with the high-concentration ozone-containing gas at a deeper part in the treatment liquid 52. Thus, the highly water-absorbent polymer, hemicellulose, lignin, and the like can be decomposed, dissolved in the treatment liquid 52, and removed from the pulp fibers.

[0195] In the present embodiment, as one of the methods, the above-mentioned delivery process includes a process of delivering the ozone-containing gas in the form of micron bubbles or nano bubbles. Among them, micron bubbles refer to bubbles with a diameter of approximately 1μm to 1000μm, preferably approximately 10μm to 500μm, and nano bubbles refer to bubbles with a diameter of approximately 100nm to 1000nm, preferably approximately 100nm to 500nm. Micron bubbles or nano bubbles are such tiny bubbles that have the properties of a large surface area per unit volume and a slow rising speed in the liquid. Therefore, in the present method, as one of the methods, the ozone-containing gas with such tiny bubbles is delivered from the lower part of the treatment liquid 52 of the treatment tank 31 to the upper part.

[0196] Since the area occupied by the tiny bubbles on the surface of the pulp fiber is relatively narrow, more bubbles can be brought into contact with the surface of the pulp fiber. Thus, the pulp fiber, the super absorbent polymer, and the connecting structure can be wrapped without omission by the tiny bubbles, and their contact area with the ozone-containing gas can be further increased. In addition, in the ozone treatment step, when the pulp fiber contents are lowered, by bringing more bubbles into contact with the surface of the pulp fiber, the buoyancy of the bubbles can be utilized to reduce the sedimentation of the pulp fiber, the super absorbent polymer, and the connecting structure, and the contact time of the pulp fiber, the super absorbent polymer, and the connecting structure with the ozone-containing gas can be further increased. Thus, the super absorbent polymer, hemicellulose, lignin, etc. can be decomposed, dissolved in the treatment liquid 52, and removed from the pulp fiber.

[0197] In the present embodiment, as one mode, the treatment liquid 52 is an acidic aqueous solution, for example, an acidic aqueous solution with a pH of 2.5 or less. In this case, even if the super absorbent polymer in the pulp fiber content 51 partially retains water absorption capacity, the water absorption and swelling of the super absorbent polymer can be suppressed. As a result, the super absorbent polymer can be dissolved in the treatment liquid 52 in a short time, and the super absorbent polymer can be removed more reliably. In particular, when the treatment liquid 52 is an ozone-containing aqueous solution, since the ozone in the ozone-containing aqueous solution can be made less likely to be deactivated, the super absorbent polymer can be oxidatively decomposed in a shorter time, and hemicellulose, lignin, etc. can be decomposed.

[0198] In addition, as another preferred embodiment, the structure of the processing tank 31 can also be Figure 2 Other structures besides . Figure 3 Yes means Figure 1 A schematic diagram of another structural example of the device 2 for the ozone treatment process. Figure 2 Compared with device 2, Figure 3The device 2 of FIG. 4 is different in that the pipe 63 of the ozone treatment unit 4 has a continuous U-shaped pipe structure formed by inverting and continuously connecting two U-shaped pipes, and the delivery pump 22 is omitted. In this case, when the pipe 63 is filled with the treatment liquid 52 and the liquid level of the treatment liquid 52 in the treatment tank 31 is higher than the liquid level of the liquid in the tank of the next process connected by the pipe 63, the treatment liquid 52 is discharged to the tank of the next process through the pipe 63 under the action of the siphon principle. Therefore, if the liquid level of the treatment liquid 52 in the treatment tank 31 is made equal to the liquid level of the liquid in the tank of the next process at the initial stage before the treatment starts, when the pulp fiber content 51 is continuously supplied to the treatment tank 31 at the first flow rate by starting the treatment, the treatment liquid 52 is discharged to the tank of the next process through the pipe 63 under the condition that the second flow rate = the first flow rate under the action of the siphon principle. The liquid level of the liquid in the tank of the next step is maintained at the level before the start of the treatment during the treatment. In this case, the delivery pump 22 is not required, and the second flow rate of the delivery pump 22 does not need to be controlled.

[0199] In the present embodiment, the separation step S13 may further include a fourth separation step S37 of separating the pulp fiber raw material from the treatment liquid 52 discharged from the treatment tank 31 and a second drying step S38 of drying the separated pulp fiber raw material.

[0200] In the fourth separation step S37, there is no particular limitation on the method for separating the pulp fiber raw material from the treatment liquid 52 discharged from the treatment tank 31. For example, a method of passing the treatment liquid 52 containing the pulp fiber raw material through a mesh having a pore size of 0.15 mm to 2 mm can be cited. When the treatment liquid 52 containing the pulp fiber raw material passes through the mesh having a pore size of 0.15 mm to 2 mm, drainage containing oxidative decomposition products of highly absorbent polymers, decomposition products of hemicellulose, decomposition products of lignin, etc. passes through the mesh. On the other hand, the pulp fiber raw material remains on the mesh.

[0201] Next, in the second drying step S38, the separated pulp fiber raw material is dried using a high temperature atmosphere or hot air. The drying temperature may be, for example, 105°C to 210°C, preferably 110°C to 190°C. The drying time also depends on the drying temperature, and may be, for example, 10 minutes to 120 minutes, preferably 15 minutes to 100 minutes. Thus, the water remaining on the surface of the pulp fiber raw material is evaporated and removed, and the pulp fiber raw material with an extremely low mixing ratio of highly absorbent polymers and a high purity can be recovered. In addition, the pulp fiber raw material can be sterilized (disinfected) using a high temperature atmosphere or hot air.

[0202] In addition, in the subsequent fiber composite reinforced material production step, when the pulp fiber raw material is used in a wet state, the second drying step S38 can be omitted.

[0203] In the present disclosure, the pulp fiber raw material preferably has a hemicellulose content of less than 8.0% by mass, more preferably less than 6.0% by mass, further preferably less than 5.0% by mass, further more preferably less than 4.0% by mass, and further more preferably less than 3.0% by mass. As a result, the fiber composite reinforcement material is not prone to coloring derived from thermally denatured hemicellulose. It should be noted that the lower limit of the hemicellulose content is 0.0% by mass.

[0204] It should be noted that, in this specification, cellulose nanofibers may include cellulose nanofibers referred to as cellulose nanofibers in the technical field. For example, the average fiber diameter of the cellulose nanofibers is preferably 1 to 1000 nm, more preferably 1 to 300 nm, further preferably 1 to 200 nm, and further more preferably 1 to 100 nm. In addition, the cellulose nanofibers may also be cellulose microfibrils.

[0205] The average fiber diameter is measured by photographing the cellulose nanofibers using an electron microscope, measuring the diameters of 100 cellulose nanofibers at random from the photographed image, and taking the arithmetic average.

[0206] In the present disclosure, the pulp fiber raw material preferably has a lignin content of 0.10 mass % or less, more preferably 0.08 mass % or less, and further preferably 0.06 mass % or less. Thus, the fiber composite reinforcement material is not prone to coloring from thermally modified substances of lignin. It should be noted that the lower limit of the lignin content is 0.00 mass %.

[0207] In the present disclosure, the pulp fiber raw material preferably has a cellulose content of 87.0% by mass or more, more preferably 90% by mass or more, and further preferably 93% by mass or more. Thus, a fiber composite reinforcement material containing cellulose nanofibers is easily and conveniently formed from the pulp fiber raw material. It should be noted that the upper limit of the cellulose content of the pulp fiber raw material is 100.0% by mass.

[0208] In the present disclosure, the cellulose content, hemicellulose content, and lignin content in the pulp fiber raw material can be measured according to a known detergent analysis method.

[0209] In the present disclosure, at least a portion (preferably 20 mol% or more, more preferably 40 mol% or more, further preferably 60 mol% or more, and further more preferably 80 mol% or more) of the primary hydroxyl groups (-CH2OH groups) of the cellulose of the pulp fiber raw material is preferably not oxidized, and more preferably not oxidized to carboxyl groups. As a result, in the fiber composite reinforced material, the cellulose nanofibers easily form hydrogen bonds with other cellulose nanofibers or polar groups in the resin, and there is a tendency for the properties of the fiber composite reinforced material, such as strength, to increase.

[0210] In addition, the pulp fiber raw material preferably does not contain nitroxide radical substances such as TEMPO (2,2,6,6-tetramethylpiperidinyl-1-oxy), oxides thereof, reduced products thereof, and the like from the viewpoint of safety.

[0211] In the present disclosure, the pulp fiber raw material preferably has a beating rate reduction speed of 300 mL or more, more preferably has a beating rate reduction speed of 320 mL or more, further preferably has a beating rate reduction speed of 340 mL or more, and further more preferably has a beating rate reduction speed of 360 mL or more. Thus, the pulp fiber raw material is easy to fluff and cellulose nanofiberization in the subsequent fiber composite reinforcement material manufacturing step, etc.

[0212] In the method for producing pulp fiber raw materials of the present disclosure, the pulp fiber raw materials preferably have a beating rate reduction rate of 990 mL or less, more preferably have a beating rate reduction rate of 800 mL or less, further preferably have a beating rate reduction rate of 700 mL or less, and further more preferably have a beating rate reduction rate of 600 mL or less. By setting in this way, it is possible to suppress damage to the pulp fiber raw materials and the cellulose nanofibers formed from the pulp fiber raw materials.

[0213] It should be noted that the above-mentioned beating degree reduction rate is obtained by, for example, low hemicellulose content and low lignin content in the pulp fiber raw material.

[0214] The freeness reduction rate is measured according to the following freeness reduction test.

[0215] <Being degree reduction test>

[0216] (1) The pulp fiber raw material is beaten for 1 hour or more, preferably 2 hours, in accordance with JIS P 8221-1: 1998 Pulp - Beating method - Part 1: Beater method.

[0217] (2) After the beating begins, samples are collected every 20 minutes, and the beating degree (Canadian Standard freeness) of each sample is measured according to JIS P 8121-2:2012 Pulp - Test Method for Freeness - Part 2: Canadian Standard Freeness Method. It should be noted that the test may be stopped when the beating degree of the sample exceeds 100 mL.

[0218] (3) Time (h) is marked on the horizontal axis, and beating degree (mL) is marked on the vertical axis. The function is approximated as a linear function using the least squares method, and the absolute value of its slope is used as the beating degree reduction rate (mL / m).

[0219] It should be noted that, with respect to the beating degree reduction rate, a larger value means that the beating degree per unit time decreases faster, that is, the pulp fiber raw material is easier to be beaten (easier to fluff).

[0220] When the pulp fiber raw material is subjected to cellulose nanofibrillation by a wet method, the pulp fiber raw material preferably has a water contact angle of less than 20°, more preferably has a water contact angle of less than 15°, and further preferably has a water contact angle of less than 10°. By setting it in this way, the pulp fiber raw material manufactured by the manufacturing method can be simply dispersed in an aqueous solution after being dried and stored. It should be noted that, from the above viewpoint, the water contact angle of the pulp fiber raw material can also be 0°.

[0221] The water contact angle of pulp fiber raw material can be measured as follows.

[0222] (1) An aluminum ring (outer diameter: 43 mm, inner diameter: 40 mm, height: 5 mm) and a pulp fiber raw material dried at 120°C for 60 minutes were prepared in a constant temperature and humidity chamber at a temperature of 20±5°C and a humidity of 65±5%RH and allowed to stand for 24 hours.

[0223] (2) 1.5 g of pulp fiber raw material was uniformly filled into an aluminum ring, and the pulp fiber raw material and the aluminum ring were compressed together at a pressure of 3 MPa for 1 minute using a press machine with a smooth bottom surface to smooth the surface of the pulp fiber raw material.

[0224] (3) The water contact angle of the compressed pulp fiber raw material was measured according to 6. The sessile drop method of "Wettability test method of substrate glass surface" of JIS R 3257:1999. As a contact angle measuring device, an automatic contact angle measuring instrument CA-V manufactured by Kyowa Interface Science Co., Ltd. can be cited. The water contact angle is the value 200ms after the deionized water is added.

[0225] (4) The water contact angles of 20 different samples were measured and their average value was used.

[0226] In the present disclosure, the pulp fiber raw material preferably has an ash content of 0.65% by mass or less, more preferably has an ash content of 0.50% by mass or less, further preferably has an ash content of 0.30% by mass or less, further more preferably has an ash content of 0.20% by mass or less, and further more preferably has an ash content of 0.10% by mass or less. By setting it in this way, when the pulp fiber raw material is subjected to cellulose nanofiberization, the metal ions and their precipitates are not likely to damage the equipment, and the metal ions and their precipitates are not likely to hinder the refinement of the pulp fiber raw material.

[0227] The ash content can be reduced by selecting an acid, particularly citric acid, that can form a complex with metal ions contained in excrement as an inactivating agent in the inactivation step S31 for inactivating the super absorbent polymer.

[0228] In this specification, ash refers to the amount of inorganic or non-combustible residues remaining after organic matter is ashed, and ash rate refers to the proportion (mass ratio) of ash contained in the material to be promoted. The above ash rate is measured according to "5. Ash Test Method" of "2. General Test Method" of the Standard for Materials of Physiological Treatment Products. Specifically, the ash rate is measured as follows.

[0229] (1) A crucible made of platinum, quartz or magnet is pre-heated at 500°C to 550°C for one hour, and its mass is precisely measured after natural cooling.

[0230] (2) Collect 2 g to 4 g of pulp fiber raw material dried at 120°C for 60 minutes and put it into a crucible. Accurately measure its mass. If necessary, remove or stagger the lid of the crucible. First, heat it weakly, then slowly increase the temperature. Burn it at 500 to 550°C for more than 4 hours until it is reduced to ashes without any carbide remaining.

[0231] (3) After natural cooling, the mass is precisely measured. The residue is ashed again until it becomes constant, and after natural cooling, the mass is precisely measured to obtain the ash content (mass %).

[0232] In the present embodiment, as one mode, an inactivation step S31 of treating the mixture with an aqueous solution capable of inactivating the water absorption performance of the super absorbent polymer to inactivate the water absorption performance of the super absorbent polymer in the mixture is further included before the ozone treatment step S36 (continuous treatment step) and a first separation step S32 of separating the inactivated super absorbent polymer and pulp fibers from the aqueous solution before the ozone treatment step S36 (continuous treatment step). In this way, in the present method, as one mode, since the water absorption performance of the super absorbent polymer is suppressed by using the aqueous solution capable of inactivating the water absorption performance of the super absorbent polymer in the inactivation step S31, the super absorbent polymer can be more easily dissolved in the treatment liquid 52 in a shorter time at the stage of the ozone treatment step S36 (continuous treatment step) in the subsequent step.

[0233] In the present embodiment, as one mode, in the inactivation step S31, the aqueous solution capable of inactivating the water absorption performance of the super absorbent polymer is an acidic aqueous solution, for example, an acidic aqueous solution with a pH of 2.5 or less. Thus, in the present method, as one mode, since the aqueous solution capable of inactivating the water absorption performance of the super absorbent polymer is an acidic aqueous solution, the super absorbent polymer is more easily inactivated, and thus, the water absorption performance of the super absorbent polymer can be more reliably suppressed at the stage of the inactivation step S31. As a result, at the stage of the ozone treatment step S36 (continuous treatment step) in the subsequent step, the super absorbent polymer can be more easily dissolved in the treatment liquid in a shorter time.

[0234] In addition, as another embodiment, the processing tank 31 may include at least a first processing tank 31 - 1 and a second processing tank 31 - 2 which are connected in series with each other. Figure 4 Yes means Figure 1 A schematic diagram of another structural example of the device 2 for the ozone treatment process. Figure 2 Compared with device 2, Figure 4The apparatus 2 is different in that the two ozone treatment sections 4 are connected in series, in other words, the first treatment tank 31-1 and the second treatment tank 31-2 are connected in series. In this case, for example, the pulp fiber content 51 is treated in multiple stages in the following manner, that is, the pulp fiber content 51 is supplied to the first treatment tank 31-1 and the first treated liquid (the treatment liquid 52-1 of the first treatment tank 31-1) is discharged, and the first treated liquid is supplied to the second treatment tank 31-2 and the second treated liquid (the treatment liquid 52-2 of the second treatment tank 31-2) is discharged. In this case, compared with the case of having one treatment tank 31 with a larger capacity, since the first treatment tank 31-1 and the second treatment tank 31-2 are treated with new treatment liquids 52-1 and 52-2, respectively, for example, the super absorbent polymer that is not completely dissolved in the first treatment tank (primary treatment tank) 31-1 can be easily dissolved in the second treatment tank (secondary treatment tank) 31-2, etc., and the super absorbent polymer can be dissolved more reliably and removed from the fibers.

[0235] In addition, as one of other modes, the treatment tank 31 may also be provided with an ejector. For example, the ejector is provided with a driving fluid supply port, a mixed fluid ejection port connected to the treatment tank, and a suction fluid supply port therebetween, and the pulp fiber content 51 is supplied to the driving fluid supply port of the ejector while ozone is supplied to the suction fluid supply port, and a mixed liquid formed by mixing the pulp fiber content 51 and ozone in the ejector is ejected from the mixed fluid ejection port into the treatment liquid in the treatment tank.

[0236] By supplying the pulp fiber content 51 as a driving fluid and the ozone as a suction fluid to the ejector and mixing them in the ejector, a mixed liquid as a mixed fluid in which the pulp fiber content 51 and the ozone are very fully mixed can be efficiently formed. That is, a mixed liquid in which the pulp fiber content 51 and the ozone are in extremely close contact can be formed. Then, by ejecting the mixed liquid into the treatment liquid in the treatment tank, the treatment liquid can be stirred. Moreover, when the ozone is ejected into the treatment liquid, it is continuously ejected in the form of fine bubbles, so it can be diffused extremely widely in the treatment liquid. As a result, the reaction between the highly absorbent polymer and the gaseous substance can be extremely efficiently carried out not only in the pulp fiber content 51 in the mixed liquid ejected from the ejector, but also in the pulp fibers containing the highly absorbent polymer in the treatment liquid in the treatment tank.

[0237] In this embodiment, as one of the methods, further, in the material separation process S1, the pre-treatment process S11 can be used to make the used sanitary products maintain their original shape without breaking, etc. and form a state that is very swollen under the action of water without inactivating the super absorbent polymer. As a result, a very high internal pressure can be generated in the used sanitary products, forming a state in which any part of its surface is about to burst. Then, by using the decomposition process S12, by applying a physical impact to the used sanitary products in this state, any part of its surface can be cracked and the internal absorbent core can be ejected to the outside. As a result, the used sanitary products can be decomposed into at least a film (non-liquid-permeable sheet) and an absorbent core. At this time, since the film roughly maintains its original shape, it can be easily separated from the absorbent core in the subsequent separation process S13. As a result, a component such as a film can be separated from other components in a manner that it maintains its original shape without breaking. Therefore, a component such as a film of sanitary products can be effectively recycled.

[0238] In this embodiment, as a preferred mode, by using terpenes for the removal of adhesives, the hot melt adhesive used for bonding the components of sanitary products can be dissolved under normal temperature conditions. Thus, it is easy to make sanitary products simply and beautifully spread, pulp fibers and highly absorbent polymers can be separated from sanitary products, and non-woven fabrics and films can be separated while retaining the component forms. That is, even if the sanitary products are not crushed or do not undergo a complicated separation process, pulp fibers, films, and non-woven fabrics can be easily recycled respectively. In the case of using limonene as a terpene, as a side effect of limonene, there is a refreshing smell of citrus, so the odor from excrement can be covered to a certain extent, and the burden of odor on the operator and the impact of odor on the vicinity can be reduced. Since limonene is a monoterpene and is similar to styrene in structure, it is possible to dissolve the styrene hot melt adhesive commonly used in sanitary products. Since sanitary products can be cleaned at room temperature, energy costs can be reduced and the generation and diffusion of odor can be suppressed. Terpenes have a high oil cleaning effect. In addition to the dissolving effect of hot-melt adhesives, if there is printed matter on the film, it can also decompose and remove the printing ink, and the printed film can also be recycled as a higher-purity plastic raw material.

[0239] In addition, when an organic acid aqueous solution with a pH of 2.5 or less is used for inactivation of a highly absorbent polymer, pulp fibers are less likely to deteriorate. In addition, when citric acid is used as an organic acid, the chelating effect and cleaning power of citric acid can be used to remove dirt components from excrement. In addition, a sterilization effect and a deodorization effect on alkaline odors can also be expected.

[0240] Furthermore, by using ozone to oxidatively decompose the super absorbent polymer, it is possible to prevent the contamination of the pulp fiber and the rapid increase of sewage caused by the super absorbent polymer absorbing water. By adjusting the concentration of ozone, it is possible to simultaneously perform oxidative decomposition and sterilization of the super absorbent polymer. In addition, when using ozone, since no chlorine-based reagents are used, it is also possible to use the recycled plastic components to manufacture high-quality RPF that is not easy to damage the combustion furnace. Since no salts are used in the processing process, there is no residue on the pulp fiber, and high-quality pulp fiber raw materials can be recovered with low ash content.

[0241] The above fiber composite reinforced material manufacturing steps are as follows Figure 1 As shown, the dried pulp fiber raw material obtained in the second drying step S38 can be supplied to the fiber composite reinforced material manufacturing step to manufacture the fiber composite reinforced material, or the undried (wet state) pulp fiber raw material obtained in the fourth separation step S37 can be supplied to the fiber composite reinforced material manufacturing step to manufacture the fiber composite reinforced material, or the treated liquid 52 containing the pulp fiber raw material obtained in the ozone treatment step S36 can be supplied to the fiber composite reinforced material manufacturing step to manufacture the fiber composite reinforced material.

[0242] The fiber composite reinforcement material production step can be carried out, for example, by mixing the pulp fiber raw material and the resin according to a method known in the art. Examples of the known method include the dry mixing method described in Patent Document 2.

[0243] In addition, the above-mentioned fiber composite reinforced material manufacturing steps are as follows Figure 1 As shown, cellulose nanofibers are formed from pulp fiber raw materials, treatment liquid 52 containing pulp fiber raw materials obtained in ozone treatment step S36, treatment liquid 52 containing pulp fiber raw materials obtained in ozone treatment step S36, etc. using a known method, and the cellulose nanofibers and resin are mixed using a known method to form a fiber composite reinforced material containing cellulose nanofibers.

[0244] It should be noted that known methods for forming the above-mentioned cellulose nanofibers include, for example, the methods described in Japanese Patent Application Publication Nos. 2010-235681 and 2010-254726, and the methods of mechanically opening the above-mentioned pulp fiber raw materials as described in Japanese Patent Application Publication No. 2008-248093.

[0245] Examples of known methods for mixing the cellulose nanofibers and the resin include the method described in JP-A-2012-229350 and a melt kneading method.

[0246] As the resin, any resin used as a resin for fiber composite reinforcement materials in the technical field can be adopted without particular limitation, and examples thereof include synthetic resins (eg, thermosetting resins, thermoplastic resins), non-biodegradable resins, and natural resins.

[0247] Examples of the thermosetting resin include epoxy, modified epoxy, unsaturated polyester, polyimide, bismaleimide, melamine, and urea.

[0248] Examples of the thermoplastic resin include polyolefins, polyamides, polycarbonates, polyphenylene sulfide, and polyetheretherketone.

[0249] The above resin may be a biodegradable resin or a marine biodegradable resin.

[0250] Examples of the biodegradable resin include polylactic acid, polybutylene succinate, polybutylene terephthalate-adipate, modified polyethylene terephthalate, polycaprolactone, polyglycolic acid, polyvinyl alcohol, polyhydroxyalkanoate, bacterial cellulose, chitosan / cellulose / starch, cellulose acetate, and esterified starch.

[0251] Examples of the marine biodegradable resin include poly(3-hydroxybutyrate)-based resins described in JP-A-2017-132967 and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate).

[0252] The fiber composite reinforcement material may be in any form, such as pellets, films, fibers, fabrics (such as nonwoven fabrics, woven fabrics, knitted fabrics), and the like.

[0253] Example

[0254] [Production Example 1]

[0255] according to Figure 1 and Figure 2 The method shown in the figure produces pulp fiber raw materials using various types of used disposable diapers collected from nursing facilities. The conditions related to the ozone treatment step S36 are as follows.

[0256] (i) Pulp fiber content 51

[0257] Concentration: 1 mass % (concentration of pulp fiber and super absorbent polymer)

[0258] pH: 2.4

[0259] (ii) Treatment tank 31

[0260] Capacity: 60L

[0261] Height: 2.6m

[0262] ·1st flow rate: 2L / min

[0263] · Second flow rate: 2L / min

[0264] · Treatment time in the tank: 30 minutes

[0265] V / W: 100

[0266] ·R O / V:0.033

[0267] (iii) Ozone-containing gas

[0268] Ozone concentration: 200g / m 3

[0269] ·Form: Nanobubbles

[0270] The inactivation step S31 was carried out with citric acid at pH 2.0, and the ozone treatment step S36 was carried out under the above conditions. The obtained pulp fiber raw material was dried at 120° C. for 60 minutes to obtain pulp fiber raw material No. 1.

[0271] [Reference Production Example 1]

[0272] Pulp fiber raw material No. 2 was obtained in the same manner as in Production Example 1 except that the treatment time in the tank was changed to 15 minutes.

[0273] [Comparative Production Example 1]

[0274] Unused pulp fibers of NBKP were used as pulp fiber raw material No. 3.

[0275] [Example 1, Reference Example 1 and Comparative Example 1]

[0276] The cellulose content, hemicellulose content, lignin content (mass %), water contact angle (°), ash content (mass %), beating rate reduction rate (mL / h), and beating rate (mL) after beating for a specified time in the beating rate reduction test of pulp fiber raw materials No. 1 to No. 3 were measured according to the beating rate reduction test described in this specification. The results are shown in Table 1.

[0277] [Table 1]

[0278] Table 1

[0279] Example No. Example 1 Reference Example 1 Comparative Example 1 Pulp raw material fiber No. No.1 No.2 No.3 Ozone treatment have have none Cellulose content (mass %) 92.7 89.9 89.8 Hemicellulose content (mass %) 7.1 10.0 10.1 Lignin content (mass %) <0.10 <0.10 0.16

[0280] Description of Reference Numerals

[0281] 31 Processing Tanks

[0282] 32 Pulp fiber content supply port

[0283] 33 Treatment fluid outlet

[0284] 43 Ozone-containing gas supply port

[0285] 51 Pulp fiber contains

[0286] 52 Treatment fluid

[0287] 53 Ozone-containing gas

[0288] S36 Ozone treatment process

Claims

1. A method for producing pulp fiber raw materials for fiber composite reinforcement materials containing cellulose nanofibers from pulp fibers to be processed, characterized in that: The method includes a pulp fiber raw material forming step of forming the pulp fiber raw material having a hemicellulose content of less than 8.0 mass % from the pulp fibers to be treated by supplying ozone-containing gas to a treatment liquid containing the pulp fibers to be treated.

2. The method according to claim 1, wherein: The pulp fiber raw material has a lignin content of 0.10 mass % or less.

3. The method according to claim 1 or 2, wherein: The pulp fibers to be treated are pulp fibers contained in used sanitary products.

4. The method according to claim 1 or 2, further comprising a fiber composite reinforced material manufacturing step: manufacturing the fiber composite reinforced material from the pulp fiber raw material and resin.

5. The method according to claim 4, wherein: In the fiber composite reinforced material manufacturing step, the pulp fiber raw material and the resin are mixed to disperse the cellulose nanofibers derived from the pulp fiber raw material in the resin.

6. The method according to claim 5, wherein: The pulp fiber raw material and the resin are mixed in a dry manner.

7. A pulp fiber raw material, characterized in that: It is a pulp fiber raw material for fiber composite reinforcement materials containing cellulose nanofibers. The pulp fiber raw material is derived from used sanitary products containing pulp fibers, The pulp fiber raw material has a hemicellulose content of less than 8.0 mass %.

8. The pulp fiber raw material according to claim 7, wherein: The pulp fiber raw material has a lignin content of 0.10 mass % or less. 9 . A fiber composite reinforcement material comprising a resin and cellulose nanofibers derived from the pulp fiber raw material according to claim 7 or 8 .

10. A pellet comprising the fiber composite reinforcement material according to claim 9.

11. A film comprising the fiber composite reinforcement material according to claim 9.

12. A fiber comprising the fiber composite reinforcement material according to claim 9.

13. A nonwoven fabric comprising the fiber composite reinforcement material according to claim 9.

Citation Information

Patent Citations

  • Method for producing phenol resin composition

    JP2008248093A

  • Method for manufacturing cellulose nano-fiber

    JP2010235681A

  • Method for producing fine fibrous cellulose

    JP2010254726A

  • Resin composition

    JP2012229350A

  • Method for producing recycled pulp from used sanitary product

    JP2016000881A